Pengaruh Citra Merek Dan Price Discount Terhadap Keputusan Pembelian Pada Produk “Jims Honey (Studi Kasus Pada Konsumen Jims Honey Di Kecamatan Cikarang Barat Kabupaten Bekasi) - Utami, Renisya Ayu; Muzaka, Erpin (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research uses quantitative research methods. The population and sample amounted to 150 consumers buying Jims Honey products. Based on the research results, the regression equation was obtained, namely Y = 3.078 + 0.610 X1 + 0.604 The research results show that there is a positive and significant influence between brand image (X1) on purchasing decisions (Y) with an R Square coefficient value of 0.299 or 29.9%. The price discount variable shows that there is a positive and significant influence between price discount (X2) on purchasing decisions (Y) with an R Square coefficient value of 0.311 or 31.1%. The brand image (X1) and price discount (X2) variables show that there is a positive and significant influence on purchasing decisions (Y) with an R Square coefficient value of 0.371 or 37.1%. It can be concluded that brand image and price discount partially and together have a positive and significant influence on purchasing decisions when purchasing Jims Honey products in West Cikarang District, Bekasi Regency.